PHILOSOPHICAL REFLECTION ON THE INTERCONNECTION OF LIFE, RELIGION, AND HISTORY: A CRITICAL APPROACH TO HISTORICAL WRITING - Abdullah Abdul Kadir; Muhammad Alwi; Hasyim Adnani; Tismat Tismat (Sekolah Tinggi Agama Islam Sadra, 2023)
Our life and religion always need history, but how historical experience leaves messages, understood and written, and obtains the status of historical truth is a fairly long discussion. History/historical writing is the relationship between the author (subject) and object (historical events/facts). This relationship is a dialectical relationship that influences the elements of truth because like it or not, humans are historians and the writing of history is directed by the individual of its recorder. It is often said that history is written by the victorious groups. By using a critical approach, structuralism (Michel Foucault), to look at episteme (suppositions and principles that unconsciously influence history and historical writers, as well as systems of thought that direct how to practice science in an era), through structuration (Antony Gidden), which shows how the structure of society and activities including writing are formed, where these conditions play a role in a discourse and determine how a discourse occurs. constructivism (J. Piaget), which directs the human way of thinking from assimilation, accommodation, and equilibrium, as well as the subjective-objective approach (philosophy), and phenomenology from Heidegger and others, to reveal the structure of know and human knowledge, thus revealing the dialectic of neurotic and its neomatic elements, elements as ‘wesen’, essence, of the true history. In conclusion, even though history is written subjectively (the human element with its history) with a subjective-objective approach, you will get history or historical writing that is quite accountable and valid. Furthermore, the hope is to present objective (Islamic) history (Islam that is generally accepted, not just because of faith, but more in a rational-objective direction) with quite valid historical evidence.